Photopolymerization of cell-laden gelatin methacryloyl hydrogels using a dental curing light for regenerative dentistry. Issue 3 (March 2018) - Monteiro, Nelson; Thrivikraman, Greeshma; Athirasala, Avathamsa; Tahayeri, Anthony; França, Cristiane M.; Ferracane, Jack L.; Bertassoni, Luiz E.
Highlights: The chemistry of gelatin methacryloyl (GelMA) was adjusted to enable photopolimerization of cell-laden hydrogels using a dental curing light. The light parameters used preserved the viability of odontoblast-like cells. This approach will be useful for chair-side procedures in regenerative dentistry. Abstract: Photopolymerized hydrogels, such as gelatin methacryloyl (GelMA), have desirable biological and mechanical characteristics for a range of tissue engineering applications. Objective: This study aimed to optimize a new method to photopolymerize GelMA using a dental curing light (DL). Methods: Lithium acylphosphinate photo-initiator (LAP, 0.05, 0.067, 0.1% w/v) was evaluated for its ability to polymerize GelMA hydrogel precursors (10% w/v) encapsulated with odontoblast-like cells (OD21). Different irradiances (1650, 2300 and 3700 mW/cm 2 ) and photo-curing times (5–20 s) were tested, and compared against the parameters typically used in UV light photopolymerization (45 mW/cm 2, 0.1% w/v Irgacure 2959 as photoinitiator). Physical and mechanical properties of the photopolymerized GelMA hydrogels were determined. Cell viability was assessed using a live and dead assay kit. Results: Comparing DL and UV polymerization methods, the DL method photopolymerized GelMA precursor faster and presented larger pore size than the UV polymerization method. The live and dead assay showed more than 80% of cells were viable when hydrogels were photopolymerized with the different DL irradiances. However, the cell viability decreased when the exposure time was increased to 20 s using the 1650 mW/cm 2 intensity, and when the LAP concentration was increased from 0.05 to 0.1%. Both DL and UV photocrosslinked hydrogels supported a high percentage of cell viability and enabled fabrication of micropatterns using a photolithography microfabrication technique. Significance: The proposed method to photopolymerize GelMA cell-laden hydrogels using a dental curing light is effective and represents an important step towards the establishment of chair-side procedures in regenerative dentistry.